An updated narrative review on revolutionizing erectile dysfunction treatment: the crucial role of trophic factors in Adipose-Derived stem cell therapy - Armaghan Ghavam; Farhad Sheikhnia; Mohammad Mahdi Heidari; Mohammad Valilo; Zanyar Mahmoudnejad; Serap Gur (BMC Urology)
Abstract Erectile dysfunction (ED) is a pervasive condition projected to affect some 322 million men worldwide by 2025, profoundly impairing quality of life and psychosocial well‑being. Current therapies—most notably phosphodiesterase‑5 inhibitors and mechanical devices—offer only transient, symptomatic relief and do not repair the underlying vascular, smooth muscle, and neural degeneration driving ED, particularly in diabetic and neurogenic subtypes. Emerging non‑cellular modalities (e.g. low‑intensity pulsed ultrasound or shockwave therapy) likewise lack demonstrated long‑term safety and durable efficacy. Adipose‑derived stem cell (ADSC) therapy has emerged as a promising regenerative strategy. In preclinical models, ADSCs exert paracrine effects—secreting trophic factors (VEGF, IGF‑1, SDF‑1, NGF) and exosomal microRNAs—that stimulate angiogenesis, smooth muscle restoration, and nerve regeneration. Innovative delivery platforms (thermosensitive hydrogels, size‑controlled spheroids, magnetic guidance) and genetic enhancements (iNOS or PEDF overexpression) further improve cell retention and functional outcomes. Early-phase clinical trials confirm ADSC safety and suggest improvements in International Index of Erectile Function scores, but are limited by small cohorts, heterogeneous protocols, and short follow‑up. Critical gaps persist that hinder translation to routine practice: the long‑term safety and efficacy of ADSC therapy remain unestablished; retention of transplanted cells in target tissues is inconsistent; methods for cell isolation, processing, dosing, delivery routes, and outcome monitoring are highly variable; and potential adverse effects—immunogenic responses or malignant transformation—have not been fully characterized. Moreover, standardized, mechanism‑based biomarkers and regulatory frameworks are lacking. To bridge these gaps, next‑generation approaches are under investigation: ADSC‑derived exosomes as cell‑free therapeutics; genetic or epigenetic modification of ADSCs to boost reparative potency; and combination regimens pairing ADSCs with adjunct modalities such as low‑intensity shockwave therapy. Rigorous, well‑powered phase II/III trials with standardized protocols, long‑term follow‑up, and mechanistic endpoints are urgently needed to validate efficacy, ensure safety, and establish best‑practice guidelines. Addressing these unmet needs could shift ED management from palliative symptom relief toward true tissue regeneration and durable cure. Graphical abstract Intra‑cavernosal injection (ICI) of adipose‑derived stem cells (ADSCs) ameliorates erectile dysfunction via multiple synergistic mechanisms. ADSCs differentiate into neurons, smooth muscle cells, and endothelial cells, thereby contributing directly to tissue regeneration. In addition, their paracrine activity results in the secretion of numerous trophic factors and exosomes that stimulate angiogenesis, neurogenesis, and nerve regeneration while concurrently suppressing inflammation. Collectively, these effects culminate in enhanced erectile function